While this is not the complete definition, an exponential expression has the variable (for example, "x") in the exponent.
(X) x (4) x (8) x (12) = 384 X
x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
x(x4+x3+x2+x+1)
In both cases, there are 2 significant figures.
It is -4.
Without an equality sign the given terms can't be classed as an equation and so therefore the value of x can not be determined.
While this is not the complete definition, an exponential expression has the variable (for example, "x") in the exponent.
Oh, dude, that's like a lot of x's and t's and some random letters thrown in there. So, technically, if you add all the x's, you get 7x, add all the t's, you get 3t, and the random letters are just there for decoration, I guess. So, the sum of x plus x plus x plus x plus x plus x plus x plus t plus t plus t plus jjakw is 7x + 3t + jjakw.
(X) x (4) x (8) x (12) = 384 X
4X
x + x + 1 + x + 2 + x + 3 = -144x + 6 = 144x = 8x = 2
It is 123.99
x+x+1+x+2+x+25=845 4x+28=845 4x=817 x=204.25
x=27
X= 5
x(x4+x3+x2+x+1)